LC/MS Analysis and ACE Inhibition Activity of Aqueous and Solvent Extracted Fractions of Selaginella bryopteris from Different Geolocations - Srivastava, Utkarsha; Mathur, Ashwani (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Pteridophytes from different demographic locations are attracting scientific interest for exploration of environment mediated changes in their phytocompound compositions, with therapeutic and commercial importance. Selaginella bryopteris (L.) Baker is one such lithophytic pteridophyte that is endemic to Indian sub-continent. It is rich in a range of phytocompounds, including flavonoids and phenolics, some of which have been reported for their therapeutic properties including neuroprotection. The current work focused on a comparison of the composition and angiotensin converting enzyme (ACE) inhibition activities of three different geographical variants of S. bryopteris from Indian deccan terrain. The phytochemical and extraction yield analysis revealed the highest methanolic extract of 81.3 mg/g of dry plant. The methanolic fraction of germplasm was analysed by liquid chromatography-mass spectrometry and was rich in flavonoids and phenolics. The presence of important flavonoids, such as narignenin, may also be responsible for relatively high ACE inhibition activity of nearly 91%, which was found for all the extracts. In-silico toxicity analysis using ProTox 3.0 revealed the presence of less toxic phytocompounds (class 4 and 5). The pharmacokinetic studies using Swiss ADME suggested the pivotal role of phytocompounds in cardioprotective and neuroprotective properties. The study may be further extended for optimization of cultivation strategies for generation of phytocompound rich plant biomass.